(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
The article considers theoretical and methodological aspects of logistics, namely logistics processes, logistics chain, logistics system, logistics management, logistics risk. A method of logistics management as an integrated process using the so-called network planning is proposed. This method allows a systematic approach to planning and managing the process of developing a new complex system. The process itself is seen as a single, inseparable process of interdependent operations aimed at achieving the ultimate goal. When analyzing the network model, a quantitative assessment of the time and cost of work performed. Elements of risk management in the logistics of enterprises using qualitative and quantitative analysis are considered.